RCM modeling of bubble injections into the inner magnetosphere: geosynchronous orbit and the ionospheric responses - Sadeghzadeh, Sina; Yang, Jian; Toffoletto, Frank; Wolf, Richard; Mousavi, Ameneh; Wang, Chih-Ping (Frontiers in Astronomy and Space Sciences, 2023)
Accurate characterization of the plasma sheet source population in the ring current region and its outer boundary at geosynchronous orbit is crucial for understanding the dynamics of the Earth's magnetosphere. Since the ring current also interacts with plasma populations from the ionosphere, this is a focus of extensive research. Using the Rice Convection Model (RCM), we simulate the transient meso-scale injections of fast flows or plasma sheet bubbles from the outer boundary into the inner magnetosphere and the associated impacts on the ionosphere. We find both quantitative and qualitative agreements and disagreements when comparing our simulation results of the average properties of bulk plasma access to geosynchronous orbit to a number of empirical models. We also examine the role of plasma sheet bubbles in forming field-aligned currents (FACs). Our modeling results show that impulsive plasma sheet injections dramatically alter the average distribution of FACs in the ionosphere. Furthermore, we demonstrate that several discrete auroral structures can be identified in the nightside ionosphere in accordance with the upward FACs.